Ḫalaqah Tradition in Building Rabbani Characters in Pesantren Al-Islam Lamongan, East Java, Indonesia - Muhammad Hambal (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
This research aims to reveal the basis of the ẖalaqah practice in the Pesantren al-Islam Lamongan, the implementation of the learning and formation of character through ẖalaqah, and the way the system may build Islamic personality. The method used in this reseach was qualitative. The results of this research are as follows. Firstly, the ẖalaqah practiced in the pesantren al-Islam was based on the ideas presented by the kyais and the management  as formulized in the khiththah  of the pesantren namely to have a rabbani generation with faith and sincerity, good morals, high spirituality, wide knowledge insights, healthy and strong physical condition, and readiness to make some propaganda about Islam. Secondly, the implementation of ẖalaqah in Pesantren al-Islam may be classified into two categories.  (1) ẖalaqah taklim, intended to give some insights to the santries on the right aqidah and the  correct worship. The employed techniques of the halaqah implementation were bandongan, sorogan  or the combination of the two. (2) ẖalaqah tarbiyah, intended to build santries to become muslims with noble morals and with some awareness and spirits of teaching  and of struggling Islam. The technique of the ẖalaqah implementation is to give materials of tazkiyat al-nafs accompanied with 'amaliah ibadah sunnah, and teaching and harakah materials and also guidance in reciting the Holy Qur'an and in guiding the characters.